An Analysis on Adultery in Hawthorne’s The Scarlet Letter - Listyowati, Rini (International Journal of English Education and Linguistics (IJoEEL), 2020)
Abstract. The main feature of the research discusses the adultery on Hester Prynne and Arthur Dimmesdale in Hawthorne’s The Scarlet Letter. Adultery is caused by several things and has impact to the doers. The research purposed is to find out the factors cause adultery done by the two main characters and the impacts on the doers. The research is qualitative research. Therefore, it applies descriptive method since the writer describes the analysis based on the data and the theories. The research uses psychological approach that just focuses on the psychological condition of adultery’s doers. The data are collected from the original text of The Scarlet Letter, then analyzed in terms of factors and impacts of adultery. The result of the research was clearly found and explained that the act of adultery is caused by several things, namely need of safety, need of affection, need of love and belongingness, and need of sex. while its impacts make the doers experience certain psychological conditions, these are esteem need, psychotic anxiety, safety need, develop superego, neurotic anxiety, mental disorder, and psychosomatic illness . The act of adultery makes the doers have different conflicts because they have different ways in facing the impacts of adultery. Hester has external conflict  such as conflict with the society, magistrates, her husband, and her child. While Dimmesadle has internal conflict  such as double avoidance conflict, double approach conflict, and approach avoidance conflict.